The blue supergiant MN18 and its bipolar circumstellar nebula - Gvaramadze, Vasilii V.; Kniazev, A. Y.; Bestenlehner, J. M.; Bodensteiner, J.; Langer, N.; Greiner, J.; Grebel, Eva K.; Berdnikov, L. N.; Beletsky, Y. (Monthly notices of the Royal Astronomical Society, 2015)
We report the results of spectrophotometric observations of the massive star MN18 revealed via discovery of a bipolar nebula around it with the Spitzer Space Telescope. Using the optical spectrum obtained with the Southern African Large Telescope, we classify this star as B1 Ia. The evolved status of MN18 is supported by the detection of nitrogen overabundance in the nebula, which implies that it is composed of processed material ejected by the star. We analysed the spectrum of MN18 by using the code cmfgen, obtaining a stellar effective temperature of ≈21 kK. The star is highly reddened, E(B − V) ≈ 2 mag. Adopting an absolute visual magnitude of MV = −6.8 ± 0.5 (typical of B1 supergiants), MN18 has a luminosity of log L/L⊙ ≈ 5.42 ± 0.30, a mass-loss rate of ≈(2.8-4.5) × 10− 7  M⊙ yr− 1, and resides at a distance of ≈5.6$^{+1.5} _{-1.2}$ kpc. We discuss the origin of the nebula around MN18 and compare it with similar nebulae produced by other blue supergiants in the Galaxy - (Sher 25, HD 168625, [SBW2007] 1) and the Large Magellanic Cloud (Sk−69$\deg$202). The nitrogen abundances in these nebulae imply that blue supergiants can produce them from the main-sequence stage up to the pre-supernova stage. We also present a K-band spectrum of the candidate luminous blue variable MN56 (encircled by a ring-like nebula) and report the discovery of an OB star at ≈17 arcsec from MN18. The possible membership of MN18 and the OB star of the star cluster Lynga 3 is discussed.
Gesehen am 17.02.2021